Regeneration dynamics of natural forest species within a stand of the invasive alien Acacia mearnsii along the Buffeljagsrivier, Swellendam, South Africa - Atsame-Edd, Angeline (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScFor)--Stellenbosch University, 2014.